"Hay que agacharse": The Embodiment of Culture in the Participant Observer Experience and the Return to the West. (7th March 2019) - Müller‐Schwarze, Nina
Abstract: Dichotomous categories, such as the West and the rest, primitive and modern, are discussed within a phenomenological theory that suggests humans create structures through which we perceive objects. The perception of culture as an object and its construction through the epistemological practices of fieldwork and interpretation within the metaphor of West and non‐Western reveals the structure of sociocultural anthropological inquiry and expresses embodiment of the cosmology of nations. Experiences of, and shared understandings regarding, the body, soul, knowledge, thoughts, emotions, memories, spirits, voice, and speech are compared from descriptions, participant observation, and embodiment as a multi‐site ethnographic performance artist expressing new genres of ethnography. Harmony is defined as social location.